La paraipotassi in italiano antico - Pesini, Luca (Premio Ricerca «Città di Firenze», 2018)
Dante's verse "If I spake false, thou falsifiedst the coin" (Inferno, Canto XXX, verse 115) is a typical example of what would later be defined as "para-hypotaxis". On the basis of a reconsideration of the categories of 'coordination' and 'subordination', the author proposes an analysis of this syntactic module in ancient Italian, addressing aspects such as its debated origin and the possibility of establishing typological comparisons with structures which are documented in other languages (outside the Romance and Indo-European spheres as well). The research focuses in particular on the identification of the discursive and textual functions of the para-hypotaxis, which were investigated in five texts from the time span between the end of the 13th century and the middle of the 16th century.